Association and predictive ability of ACTN3 C/T, ACE I/D and PPARGC1A A/G polymorphisms on jump height of elite Malaysian footballers - Choo, Yee Yu; Tan, Chee Hian; Raja Azidin, Raja Mohammed Firhad; Aiman, Suhana; Ang, Geik Yong; Saidi, Nur Fatihah (Faculty of Sports Science and Recreation (FSR) UiTM, 2024)
Footballing performance is a complicated phenotype influenced by various factors that include individual genetic makeup and environmental variables. Genetic association research in football is gaining significant interest but the majority of the studies involve Caucasian and Brazilians footballers. Therefore, this study aims to investigate the association and predictive ability of a total genotype score derived from ACTN3 C/T, ACE I/D and PPARGC1A A/G polymorphisms on jump height of elite Malaysian footballers. A total of sixty-seven elite Malaysian Malay male footballers (19.8 ± 1.4 years) participated in this study and genomic DNA was extracted from saliva samples for genotyping and calculation of the total genotype score. The jump height of each participant was assessed using the Yardstick vertical jump device. The mean jump height and total genotype score of the participant were 61.9 ± 6.5 cm and 38.8 ± 18.0, respectively. Spearman rank-order correlation indicated that a significant positive correlation was found between the total genotype score and jump height that remained significant (rs = 0.276; p = 0.027) after adjusting for height and body mass of the participants. A significant regression was found F(1, 65) = 6.554, p = 0.013 with the r2 value of 0.092 indicating that the total genotype score explained 9% of the variance in jump height. The positive association between total genotype score and jump height in elite Malaysian footballers indicated that footballers with a greater total genotype score tend to attain a higher jump height and may have further implications in football as literature has indicated that jump performance could be used to infer speed and maximal strength.